Genome Variation in the Model Halophilic Bacterium Salinibacter ruber - González-Torres, Pedro; Gabaldón, Toni (Frontiers in Microbiology, 2018)
The halophilic bacterium Salinibacter ruber is an abundant and ecologically important member of halophilic communities worldwide. Given its broad distribution and high intraspecific genetic diversity, S. ruber is considered one of the main models for ecological and evolutionary studies of bacterial adaptation to hypersaline environments. However, current insights on the genomic diversity of this species is limited to the comparison of the genomes of two co-isolated strains. Here, we present a comparative genomic analysis of eight S. ruber strains isolated at two different time points in each of two different Mediterranean solar salterns. Our results show an open pangenome with contrasting evolutionary patterns in the core and accessory genomes. We found that the core genome is shaped by extensive homologous recombination (HR), which results in limited sequence variation within population clusters. In contrast, the accessory genome is modulated by Horizontal Gene Transfer (HGT), with genomic islands and plasmids acting as gateways to the rest of the genome. In addition, both types of genetic exchange are modulated by Restriction and modification (RM) or CRISPR-Cas systems. Finally, genes differentially impacted by such processes reveal functional processes potentially relevant for environmental interactions and adaptation to extremophilic conditions. Altogether, our results support scenarios that conciliate “Neutral” and “Constant Diversity” models of bacterial evolution.